Breeding activity of the neotropical treefrog Hyla elegans (Anura, Hylidae) - Bastos, Rogério P.; Haddad, Célio F. B. [UNESP] (JSTOR, 1996)
Breeding of Hyla elegans was monitored from August 1991 to July 1992 at a temporary pond in Ubatuba, State of Sao Paulo, southeastern Brazil. Males began to call as they entered the chorus, and defended their calling sites from other males, at times with physical interactions. Females, however, were not aggressive toward either males or other females. We found a positive correlation between the numbers of females and males in the chorus, but no significant correlation between OSR (number of reproducing females/number of reproducing males) and the number of males present. OSR was highly male-biased; on average, there were 10 males for each female; this low OSR may explain low average mating success of males. Females chose males as mates freely, and males did not attempt to intercept females approaching other males. Males in amplexus were larger and heavier than unmated, calling males. In addition, snoutvent lengths of males and females in amplexus were positively correlated, and males were, on average, 0.81 the length of females. Experimentally paired males and females with smaller or larger ratios of SVLs had a lower percent of fertilization than pairs near the population average.
Keywords: Anura; Hyla elegans; Hylidae